How to write a good teaching note. Part 3 : RSM CDC case writing training material - Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
A teaching note is a valuable document that accompanies a teaching case, aiding instructors in better understanding and using the case effectively. While not mandatory for every case, statistics show that cases with teaching notes tend to be more popular. This article outlines the key components of a teaching note, emphasizes the importance of precise teaching objectives, and provides guidance on creating an effective teaching plan with discussion questions and analyses. Additionally, it discusses the audience for teaching notes and common pitfalls to avoid when writing them. Writing a comprehensive teaching note is essential for maximizing the educational value of a teaching case.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Case method -- Case studies; Lesson planning -- Case studies; Teaching -- Aids and devices -- Authorship -- Case studies